Determination of Hydrogen Peroxide (H2O2) by New Design of Continues Flow Injection Unit - Dakhil Nassir Taha (Journal of Global Pharma Technology, 2016)
This study includes the design of continues injection system to determine the hydrogen peroxide (H2O2) containing valve is designed locally and this method is quick, cheap and characterized by high accuracy. The method is based on the fast reduction of the complex compound K3[Fe(CN)6] by H2O2 in basic medium with maximum wavelength at 420 nm. Various parameters (physical and chemical) affecting on the determination have been investigated such as flow rate, volume of the loop, concentration of the complex compound and concentration of the base. The calibration curve was prepared and the dispersion coefficient, reproducibility and application were studied. The linear range was (0.06 - 0.8) % at sampling rate of 60 sample per hour, (R2=0.9923) and the detection limit at S/N=3 was 0.02%. Dispersion coefficient was also measured for the method.Keywords: Continues Injection, Determination Hydrogen peroxide H2O2.